Extraction-type tissue package as well as manufacturing method and manufacturing equipment thereof - ZHU JILIAN; WANG YAJUAN; GU CHENGHUI; HUANG JINHUA (2021)
The invention discloses an extraction-type tissue package as well as a manufacturing method and manufacturing equipment thereof. The extraction-type tissue package comprises an outer package and an extraction-type tissue stack accommodated in the outer package, wherein the extraction-type tissue stack comprises a plurality of tissues which are folded in a staggered manner; the tissues at least comprise first tissues and second tissues; and the first tissues and the second tissues are sequentially stacked in a staggered manner and have different characteristics. Through the arrangement of the extraction-type tissue stack with the tissues of different characteristics in the extraction type tissues in a unit of the extraction-type tissue package, the different function requirements and diversified use requirements of users for the tissues can be met. 本申请公开了一种抽取式纸巾及其制造方法和制造设备。该抽取式纸巾包括外包装和容置于外包装内的抽取式纸巾叠；其中，抽取式纸巾叠包括交错折叠的多个纸巾，多个纸巾中至少包括第一纸巾和第二纸巾，第一纸巾和第二纸巾依次交错层叠且具有不同的特性。通过在单位包装的抽取式纸巾中设置具有不同特性纸巾的抽取式纸巾叠中，满足用户对纸巾的不同功能需求和